Structure and Genetic Variability of the Oceanic Whitetip Shark, Carcharhinus longimanus, Determined Using Mitochondrial DNA. - Sâmia M Camargo; Rui Coelho; Demian Chapman; Lucy Howey-Jordan; Edward J Brooks; Daniel Fernando; Natalia J Mendes; Fabio H V Hazin; Claudio Oliveira; Miguel N Santos; Fausto Foresti; Fernando F Mendonça (PLoS ONE)
Information regarding population structure and genetic connectivity is an important contribution when establishing conservation strategies to manage threatened species. The oceanic whitetip shark, Carcharhinus longimanus, is a highly migratory, large-bodied, pelagic shark listed by the IUCN (International Union for Conservation of Nature) Red List as "vulnerable" throughout its range and "critically endangered" in the western north Atlantic. In 2014, the species was protected globally under Appendix II of CITES (Convention on International Trade in Endangered Species), limiting and regulating trade. This study used partial sequences of mitochondrial DNA (mtDNA) control region to determine the population genetic structure of oceanic whitetip sharks across the Atlantic and Indian Oceans. 724 base pairs were obtained from 215 individuals that identifed nine polymorphic sites and defined 12 distinct haplotypes. Total nucleotide diversity (π) was 0.0013 and haplotype diversity (h) was 0.5953. The Analysis of Molecular Variance (AMOVA) evidenced moderate levels of population structure (ɸST = 0.1039) with restricted gene flow between the western and eastern Atlantic Ocean, and a strong relationship between the latter region and the Indian Ocean. Even though the oceanic whitetip is a highly migratory animal the results presented here show that their genetic variability is slightly below average of other pelagic sharks. Additionally, this study recommends that at least two populations in the Atlantic Ocean should be considered distinct (eastern and western Atlantic) and conservation efforts should be focused in areas with the greatest genetic diversity by environmental managers.